CCL18 signaling from tumor-associated macrophages activates fibroblasts to adopt a chemoresistance-inducing phenotype - Wenfeng Zeng; Lixiong Xiong; Wei Wu; Shunrong Li; Jiang Liu; Linbing Yang; Liyan Lao; Penghan Huang; Mengmeng Zhang; Huiping Chen; Nanyan Miao; Zhirong Lin; et al. (2022)
Abstract The heterogeneity of cancer-associated fibroblasts (CAFs) might be ascribed to differences in origin. CD10 and GPR77 have been reported to identify a chemoresistance-inducing CAF subset in breast cancer. However, the precise mechanism for the formation of the CD10 + GPR77 + CAFs remains unknown. In this study, we found that CCL18 expression was positively correlated with the density of CD10 + GPR77 + CAFs in breast cancer and associated with a poor response to chemotherapy. Moreover, CCL18 secreted by tumor-associated macrophages (TAMs) activated a CD10 + GPR77 + CAF phenotype in normal breast-resident fibroblasts (NBFs), which could then enrich cancer stem cells (CSCs) and induce chemoresistance in breast cancer cells. Mechanistically, CCL18 activated NF-κB signaling via PITPNM3 and thus enhanced the production of IL-6 and IL-8. Furthermore, intratumoral CCL18 injection significantly induced the activation of NBFs and the chemoresistance of xenografts in vivo. In addition, targeting CCL18 by anti-CCL18 antibody could inhibit the formation of CD10 + GPR77 + CAFs and recover the chemosensitivity in vivo, leading to effective tumor control. Collectively, these findings reveal that inflammatory signaling crosstalk between TAMs and fibroblasts is responsible for the formation of the CD10 + GPR77 + CAFs, suggesting CCL18–PITPNM3 signaling is a potential therapeutic target to block the activation of this specific CAF subtype and tumor chemoresistance.